Factors affecting the recovery of hepatic reserve after sustained virologic response by direct‐acting antiviral agents in chronic hepatitis C virus‐infected patients. Issue 2 (11th October 2020) - Nakajima, Tomoaki; Karino, Yoshiyasu; Hige, Shuhei; Suii, Hirokazu; Tatsumi, Ryoji; Yamaguchi, Masakatsu; Arakawa, Tomohiro; Kuwata, Ysuaki; Hasegawa, Takashi; Toyota, Joji
Abstract: Background and Aim: Since the advent of direct‐acting antiviral (DAA) therapy, the total eradication of hepatitis C virus has been achievable with the recovery of hepatic reserve after achievement of sustained virologic response (SVR). Hence, here, we examined the factors affecting the recovery of hepatic reserve. Methods: We followed up 403 patients (male: 164, female: 239; genotype 1: 299, genotype 2: 104; median age: 69 years) for at least 3 years after they achieved SVR to DAA therapy. Of these patients, 75 (18.6%) had a history of hepatocellular carcinoma (HCC). Biochemical tests were periodically performed, and the hepatic reserve was evaluated based on the albumin–bilirubin grade. We examined background factors such as age, biochemical test results, HCC occurrence and portosystemic shunt by computed tomography. Results: At the start of treatment, the albumin–bilirubin grades were grades 1, 2, and 3 in 241, 157, and 5 patients, respectively, and 3 years later, 117 of 162 (72%) patients with grade 2 or 3 improved to grade 1. Multivariate analysis identified the HCC occurrence after achievement of SVR (hazard ratio [HR]: 3.08, P < 0.0138), male sex (HR: 3.45, P = 0.0143), hemoglobin level of <11.5 g/dL (HR: 4.19, P = 0.0157), the presence of a portosystemic shunt (HR: 3.07, P = 0.0349), and alanine aminotransferase levels <45 U/L (HR: 2.67, P = 0.0425) as factors inhibiting improvement to grade 1. However, old age was not an inhibitory factor. Conclusion: Our results demonstrate that hepatic reserve could be improved even in elderly patients over a long course of time.